Analisis Rasio Profitabilitas Terhadap Pertumbuhan Laba Pada Perusahaan Automotive And Allied Products Yang Terdaftar Di BEI Tahun 2011-2014 - Novisheila, Nadia Resi; , Drs.Muhammad Nasir, MM (2016)
This study aims to examine whether there is influence profitability ratios (ROA, ROE, and NPM) on corporate earings Automotive and Allied Products listed on the Stock Exchange in the period 2011-2014. this study uses a survey of secondary data with the company population Automotive and Allied Product listed in the Indonesia Stock Exchange (BEI) in 2011-2014. Criteria used to determine sample using purposive sampling of companies whose shares are actively traded during the year 2011-2014, published financial statements. With this method obtained a sample of 15 companies. The analysis technique used in consisting of normality test, mulcollinearity, autocorrelation, and heteroscedasticity test used asses the validity of the regression equaiton. In addition there is t-test, F, and the coefficient of determination. The result of this study concluded that the t test derived variables, Return on Assets (ROA) has no effect on profit growth, return on equity (ROE) has no effect on the growth of earnings, and Net Profit Margin (NPM) effect on profit growth. F test results in this study Keywords: The company's profit, Return on Asset (ROA), Return on Equity (ROE), and the Net Profit Margin (NPM) effect on profit growth. F test results in this study variables Return on Asset (ROA), Return on Equity (ROE), and the Net Profit Margin (NPM) together effect on profit growth.